2021
DOI: 10.3389/fpls.2021.649204
|View full text |Cite
|
Sign up to set email alerts
|

Growing in Mixed Stands Increased Leaf Photosynthesis and Physiological Stress Resistance in Moso Bamboo and Mature Chinese Fir Plantations

Abstract: Mixed-stand plantations are not always as beneficial for timber production and carbon sequestration as monoculture plantations. Systematic analyses of mixed-stand forests as potential ideal plantations must consider the physiological-ecological performance of these plantations. This study aimed to determine whether mixed moso bamboo (Phyllostachys pubescens (Pradelle) Mazel ex J. Houz.) and Chinese fir (Cunninghamia lanceolata (Lamb.) Hook.) stands exhibited better physiological-ecological performance than mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 85 publications
(158 reference statements)
1
5
0
Order By: Relevance
“…The leaf photosynthetic capacity decreased with increasing culm age; however, the isoprene emission rate followed the order of young >old >and mature plants. The effects of culm age on photosynthesis observed in our study are consistent with those of previous studies ( Kleinhenz and Midmore, 2001 ; Peng et al., 2021 ). As expected, young plants had the highest isoprene emission rate because the biosynthesis of isoprene is based on a photosynthetically fixed carbon ( Niinemets et al., 2002 ; Jardine et al., 2014 ; de Souza et al., 2018 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The leaf photosynthetic capacity decreased with increasing culm age; however, the isoprene emission rate followed the order of young >old >and mature plants. The effects of culm age on photosynthesis observed in our study are consistent with those of previous studies ( Kleinhenz and Midmore, 2001 ; Peng et al., 2021 ). As expected, young plants had the highest isoprene emission rate because the biosynthesis of isoprene is based on a photosynthetically fixed carbon ( Niinemets et al., 2002 ; Jardine et al., 2014 ; de Souza et al., 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…Owing to a lack of secondary development and the blocking of xylem vessels by tyloses, aged culms are particularly susceptible to xylem dysfunction; this can lead to a progressive loss of photosynthates, nutrients, and conductivity for water and, eventually, culm mortality ( Liese and Weiner, 1996 ). Moreover, leaf morphology ( Hu et al., 2021 ) and photosynthesis ( Kleinhenz and Midmore, 2001 ; Peng et al., 2021 ) depend not only on the leaf age but also on the culm age. However, whether culm age affects leaf isoprene emissions is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the distribution area, including the center area, of three Fritillaria species received the influence of monsoon from the Indian and Pacific oceans and has sufficient precipitation from May to September. Water was reported to play an essential role in root growth ( Sharma et al, 2021 ), seed dormancy and germination ( Sheppard et al, 2014 ), and leaf growth and photosynthesis ( Peng et al, 2021 ). Water deficiency would activate transcription factors and thus promote the expression of stress-related genes ( Van Beek et al, 2021 ), whereas sufficient water would increase stomatal and leaf area ( Mozo et al, 2021 ) and promote dormancy and germination ( Chritine et al, 2014 ; Sheppard et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Moso bamboo efficiently utilizes light energy to synthesize essential organic matter, contributing significantly to its rapid growth. 12 It has been reported that young bamboo shoots will perish within 10 days under complete shading treatment, 13 which highlights the importance of light for the growth of Moso bamboo. Currently, there have been notable advancements in the examination of light regulation in Moso bamboo.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, research on Moso bamboo predominantly centers on both biotic and abiotic stresses that impact its yield, including factors such as disease infestation, drought, soil salinity, temperature, and high light . Light, as a critical factor, serves not only as an energy source for photosynthesis in plants but also plays a crucial role in regulating the growth and development of plants. , Moso bamboo efficiently utilizes light energy to synthesize essential organic matter, contributing significantly to its rapid growth . It has been reported that young bamboo shoots will perish within 10 days under complete shading treatment, which highlights the importance of light for the growth of Moso bamboo.…”
Section: Introductionmentioning
confidence: 99%